Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Puskesmas Barung-Barung Balantai Kabupaten Pesisir Selatan - Bunga .; M. Afuan; Nila Pratiwi (CV. ITTC INDONESIA, 2026)
This study aims to determine and analyze the influence of work environment and compensation on employee performance with job satisfaction as an intervening variable at the Barung-Barung Balantai Community Health Center, Pesisir Selatan Regency. This study is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population of this study was 89 employees of the Barung-Barung Balantai Community Health Center, Pesisir Selatan Regency. The sampling technique in this study used saturated samples with a sample of 30 employees. The results of the study found that there was no significant influence of the work environment on job satisfaction, there was a significant influence of compensation on job satisfaction, there was a significant influence of the work environment on employee performance, there was no significant influence of compensation on employee performance, there was no significant influence of job satisfaction on employee performance, there was no significant influence of the work environment on employee performance through job satisfaction, compensation did not have a significant effect on employee performance through job satisfaction.